Angular dependence of L X-rays emission for Ag by 10 keV electron-impact. (August 2016) - Wang, Xing; Xu, Zhongfeng; Zhang, Ying; Ma, Chao; Zhu, Chengwei
Abstract: The characteristic X-ray intensities of Ag-Lα, Lβ1, Lβ2 and L γ 1 are measured in electron-impact ionization at energy of 10 keV. The emission angle in this work ranges from 0° to 20° at interval of 5°. The angular dependence of L X-ray intensity ratios has been investigated for Lα / Lβ1, Lβ2 / Lβ1 and Lγ1 / Lβ1 . It is found from the experimental results that the emissions of Lβ1, Lβ2 and L γ 1 X-rays are spatially isotropic, while the Lα X-rays exhibit anisotropic emission. Consequently, the alignment behavior of vacancy states is discussed with thorough analysis of vacancy transfer process. Highlights: Only the Lα X-rays are found to be spatially anisotropic in the measurement. The alignment of L3 -subshell is influenced by vacancy transfer process. Different alignment behaviors in previous work have been clarified.